Case report: A left forearm mass with eccentric intramedullary ulnar destruction diagnosed as alveolar rhabdomyosarcoma and treated by wide resection and free vascularized fibular graft - Yang, Chenyu; Wang, Xinjia; Lin, Huaitai; Zhu, Jinhao; Xu, Zijian; Wang, Weidong (Frontiers in Oncology, 2024)
Background Alveolar Rhabdomyosarcoma is a profoundly malignant soft-tissue sarcoma that predominantly affects children and adolescents. However, the medical field lacks consensus regarding the optimal surgical approach to be undertaken in cases where this tumor causes local bone destruction in the upper limb. Case description A 17-year-old male presented a mass in his left forearm and CT and MRI indicated that the mass had penetrated the ulnar cortex and infiltrating the medulla, resulting in the formation of an eccentric trans-ventricular tumor focus. The sizable tumor affected the volar muscles of the forearm as well as the ulnar bone marrow, exerting pressure on the ulnar artery and vein. It was confirmed by needle biopsy that the mass is alveolar rhabdomyosarcoma. Following two courses of neoadjuvant chemotherapy, the tumor was widely excised en bloc. Autologous fibula with a vascular pedicle was utilized for reconstruction during the procedure. In the postoperative follow-up, no local recurrence of the tumor was observed. Furthermore, the patient retained satisfactory wrist flexion and pronation function in the left forearm. Conclusions Alveolar rhabdomyosarcoma is an uncommon and highly aggressive form of soft tissue sarcoma. Scientific management necessitates a multidisciplinary approach, combining chemotherapy with surgery. In cases where the tumor invaded into compartment of the bone, careful consideration should be given to the boundaries of tumor resection, the extent of osteotomy, and the approach to musculoskeletal reconstruction when designing the surgical plan. Through reporting our own case and thoroughly reviewing previous clinical experiences, we aim to provide valuable insights for the treatment of this particular disease.